ANALYSIS OF EDUCATION LEVEL AND INCOME EFFECT TO THE NUMBER OF POOR INHABITANT IN INDONESIA - Syamsul Arifin (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2020)
This research aims to analyze the level of education and income per capita of the number of poor people in Indonesia in 2004 - 2019 either partially or simultaneously. The population in this study was Indonesia in 2004 - 2019. The sampling technique is purposive sampling technique. The data collection method is documentation. Although the method of analysis using regression analysis techniques of time series data. The results of data analysis showed that the level of education is partially significant effect on the number of poor people in Indonesia. On the other hand revenues significantly influence the number of poor people in Indonesia. While simultaneously the levels of education and income influence significantly to the number of poor people in Indonesia.